The influence of client attributes on project success : a focus on the briefing stage / Norizan Ahmad - Ahmad, Norizan (2008)
This study examines the briefing process of construction projects. Identifying clients' requirements and translating it into building form are the two fundamental issues of the briefing process. The attributes of the client as the key project participant during briefing is the main focus of this study. The client attributes investigated were categorized into three categories; the quality of the clients representative, brief management efforts and commitment of client organization. The influences of client attributes during the briefing process on the level of project success were analyzed. This study also investigates the factors influencing the quality of clients' attributes during briefing process. They are the characteristics of the client, the nature of the project and the quality of design team.